An on‐site digital investigation methodology for data leak case. Issue 12 (17th January 2012) - Lee, Seokhee; Lee, Keungi; Park, Jong Hyuk; Lee, Sangjin
ABSTRACT The ever growing storage device capacity poses a severe limit to the standard digital forensics collection procedures based on duplicating the original storage device by creating a bit‐by‐bit copy. Such a traditional procedure is followed, even if the goal of the investigation is to find a limited quantity of digital objects to support or refute an investigative hypothesis related to a precise case category. Therefore, in this paper, we propose a new methodology to deal with data leak cases, by applying an intelligent collection paradigm, a fast analysis approach that reduces investigation time. Copyright © 2012 John Wiley & Sons, Ltd.